2006
DOI: 10.1080/14616730600789472
|View full text |Cite
|
Sign up to set email alerts
|

Separation and loss through immigration of African Caribbean women to the UK

Abstract: This paper reports on 20 women born in the Caribbean whose birth mothers left them there as young children in the care of grandmothers or other members of their extended family. This was in order to migrate to Great Britain during the late 1950s through the 1970s in search of economic prosperity, and reunification with the father/husband already working in the UK. The reunions occurred typically more than a decade later, in the child's adolescence, when mother and child were meeting as if for the first time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…Research has shown that immigrant children who experience parent–child separation often withdraw emotionally from their parents (Dreby, ) and report impaired family relationships (Michael, ). Migrant parents often report struggling to assert their authority (Dreby, ) and difficulties establishing functional intrafamily relationships (Arnold, ). Conversely, family functioning is closely related to migrant children's psychological adaptation.…”
Section: Patterns Of Migration and Their Relationships To Psychologicmentioning
confidence: 99%
“…Research has shown that immigrant children who experience parent–child separation often withdraw emotionally from their parents (Dreby, ) and report impaired family relationships (Michael, ). Migrant parents often report struggling to assert their authority (Dreby, ) and difficulties establishing functional intrafamily relationships (Arnold, ). Conversely, family functioning is closely related to migrant children's psychological adaptation.…”
Section: Patterns Of Migration and Their Relationships To Psychologicmentioning
confidence: 99%
“…Depressive responses have been noted in both children (Rutter, 1971) and mothers (Bernhard et al, 2006;Hohn, 1996). Children may have difficulty trusting others (Arnold, 2006;Artico, 2003), and those who experienced long-term separations are more likely to receive psychiatric services (Morgan et al, 2007). Some youth may respond by externalizing, increased anger, and aggression (Burke, 1980;Dreby, 2007;Lashley, 2000;Smith, 2006;Wilkes, 1992).…”
Section: Immigrant Family Separations Researchmentioning
confidence: 99%
“…Also, children may be disappointed for how their real parents turn out to be, as compared to their fantasies and expectations about the life in the United States (Artico, 2003). After the long separation period, youth left behind feel competitive with siblings born in the host country for the mother's affection (Arnold, 2006), and parents often report having difficulties in establishing functional intrafamily relationships (Arnold, 2006;Boti & Bautista, 1999;Sewell-Coker, Hamilton-Collins, & Fein, 1985). The longer the separation they underwent, the less likely adolescents report being able to identify with their parents or being willing to conform to their rules at the time of reunification (Smith, Lalonde, & Johnson, 2004).…”
Section: Immigrant Family Separations Researchmentioning
confidence: 99%
“…From her study of twenty adult women who had been serial migrants from the Caribbean, Arnold (2001Arnold ( , 2006Arnold ( , 2011 reported painful experiences of separation from, and reunion with, their mothers that the women suggested led to difficulties in trusting other people. Most, however, considered themselves resilient in other ways.…”
Section: Serial Migration and Transnational Family Livesmentioning
confidence: 99%
“…The parents of the participants in the study left the Caribbean between the early 1950s and mid 1960s at a time when their labour was solicited in the UK (Bauer and Thompson, 2006). Since serial migration was common in Caribbean countries, it was not considered 'non-normative' in the countries in which the women had been born, or in their social circles (Arnold, 2006). The sample consisted of 39 women and 14 men (N=53), who ranged in age from the late 30s to the early 60s, with a mean age of 53 years.…”
Section: The Studymentioning
confidence: 99%